Perbandingan Antara Hukum Islam dan Hukum Positif dalam Masalah Perdata - Herlina, Herlina; Sumanto, Dedi; Sehoni, Sehoni (Journal of Legal Sustainability, 2025)
This study aims to analyze the application of the concept of khiyar (option) in modern sales transactions, particularly within the context of online commerce and the rapidly growing digital sales systems today. The concept of khiyar in Islamic law grants both sellers and buyers the right to choose to continue or cancel a contract under certain conditions to maintain justice and prevent practices that harm either party. The research method employed is a qualitative approach with normative juridical analysis, examining Islamic legal sources such as the Qur’an, Hadith, and classical as well as contemporary fiqh muamalah literature, alongside a comparison with modern sales practices, including return policies, warranty systems, and consumer protection in e-commerce. The study’s findings show that the principle of khiyar has been substantially implemented in various features of modern transactions, such as product return rights, trial periods, and customer complaint systems. However, these implementations are not yet fully aligned with the rules of fiqh muamalah, as some digital trade practices still contain elements of uncertainty (gharar) and injustice. Therefore, education and strengthening of sharia-based regulations are necessary to ensure that the exercise of khiyar rights provides fair protection for consumers and business actors in accordance with the values of Islamic law.